Enhancing Visible-Light Photocatalytic Activity of AgCl Photocatalyst by CeO2 Modification for Degrading Multiple Organic Pollutants - Li Xu; Ning Yang; Tong Xu; Yang Yang; Yanfei Lv (Nanomaterials)
A new type of CeO2-modified AgCl catalyst (CeO2/AgCl) was prepared by a one-step method, which efficiently inhibits the recombination of photogenerated carriers. During the visible-light degradation process, this catalyst exhibited excellent and stable performance. It could not only effectively degrade rhodamine B (RhB), methyl orange (MO) and crystal violet (CV) but also maintain excellent activity under different environmental conditions. In the RhB degradation experiment in particular, the CeO2/AgCl-30 composite with the optimal proportion had a degradation rate 5.43 times that of pure AgCl in the seawater system and 9.17 times that of pure AgCl in the deionized water condition, while also showing excellent stability. Through characterization tests such as XRD, XPS and ESR, its crystal structure, elemental composition and so on were analyzed. Based on the characterization results, the CeO2/AgCl composite showed a relatively wide light absorption range and a relatively high photo-induced charge separation efficiency. Meanwhile, it was inferred that the main active species in the reaction process were ·O2⁻ and ·OH. Finally, based on its electronic band structure, an S-scheme heterojunction structure was proposed.